OPTIMIZING THE GREEN PRODUCT STRATEGY IN IMPROVING MSME PERFORMANCE - Meiliyah Ariani; Melan Susanty Purnamasari; Kurnia Sari Dewi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to determine the effect of green input, green process and green output in the application of green products on the performance of UMKM in Penjaringan Subdistrict, North Jakarta. The method used is purposive sampling, the number of respondents used in this study is 100 respondents from UMKM in the food and beverage sector in Penjaringan Subdistrict, North Jakarta. The data used is primary data in the form of questionnaires distributed to respondents. The data analysis method used in this study is data analysis with descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression analysis tests, which examine variables from the data using IBM SPSS (Statistical Product and Service Solutions) for Windows version 25.The results of research and hypothesis testing show that green input in the application of green products has a positive and significant effect on the performance of UMKM, Green process in the application of green products has a positive and significant effect on the performance of UMKM, Green output in the application of green products has a positive and significant effect on the performance of UMKM.